APPLICATION OF INFORMATION RETRIEVAL ROOM IN BUILDING A8 FACULTY OF ENGINEERING SURABAYA STATE UNIVERSITY WEB-BASED AND VIRTUAL REALITY - ariszki, fatkul ikrom; Nurhayati, Nurhayati (Jurusan Teknik Elektro Fakultas Teknik UNESA, 2020)
Technology plays an important role in human life today, the ease of accessing the internet makes information technology a tool to help humans in their daily lives, one of which is a tool that can find new locations. The high use of search engines makes search engines the choice that is often used in finding information. This research was conducted to implement the Information Retrieval system to find rooms in the Engineering Faculty, Surabaya State University. The system will perform keyword indexing (query) to documents that are already stored in the MySQL database. This IR system is loaded on a Web page, equipped with general information about the room, the room's location point (Maps), and a Virtual Reality display that can provide users with a room browsing experience. The results of the study were a room search system website equipped with VR which was rated well by users with an average rating of 78%. From the results of this research, the IR web system is suitable for use as a medium to provide information and instructions for rooms in building A8, Faculty of Engineering, State University of Surabaya. In the management of information media, it is necessary to improve the quality of information and services, to support the needs of users so that information technology media can be used by users who are not familiar with the Surabaya State University environment.